Meningkatkan Kualitas Generasi Muda di Desa Jemekan Melalui Cerdas Literasi dan Berorganisasi Menuju Indonesia Bangkit 2045 - Fahraini, Sovia; Qohar, Sahal Awaludin; Sulistyowati (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
Towards Awakening Indonesia 2045, education plays a central role in forming a golden generation in Indonesia. Unfortunately, Jemekan Village faces challenges, especially in terms of literacy, young people's low interest in reading, lack of open space for reading, and unwise use of gadgets, which has a negative impact on their intellectual development. Apart from that, the lack of youth contribution to improving their quality through organizational activities is also a problem. By applying the ABCD method, IAIN Kediri KKN students play an active role in increasing digital literacy through tutoring and developing soft skills, such as learning Pegon Arabic and speech skills. This activity aims to provide different learning experiences to elementary school students, as well as support the cadre formation of the IPNU/IPPNU organization through literacy and organizational seminars in the digital era. It is hoped that this effort can support the youth of Jemekan Village in improving their intellect and self- esteem.